Worse Theory of Mind in Only-Children Compared to Children With Siblings and Its Intervention - Zhang, Zhuo; Yu, Haoxue; Long, Muyun; Li, Hui (Frontiers in Psychology, 2021)
The purpose of this study was to explore theory of mind (ToM) differences in children with different birth orders (only-children, first-born children, and second-born children), and further explore the effect of cognitive verb training for only-children’s ToM. Adopting the paradigm of false belief, Study 1 was conducted in which a sample of 120 children aged 3–6, including first-born children, second-born children (siblings aged 1–13 years), and only-children were tested. The results showed that (1) children aged 3–6 had significantly higher scores on first-order false-belief than second-order false-belief. (2) Controlling for age, the only-children scored significantly lower than the first-born children. In Study 2, 28 only-children aged 4–5 (13 in the experimental group and 15 in the control group) who initially failed in false-belief tasks were trained with the cognitive verb animations. Significant post-training improvements were observed for only-children who received training of animations embedded with cognitive verb. Those findings indicated that ToM of only-children was significantly worse than first-born children of two-child families, and linguistic training could facilitate ToM of only-children whose ToM were at a disadvantage.